On the performance of pulsed frequency modulated UWB local positioning systems - Ebelt, Randolf; Waldmann, Benjamin; Bauer, Georg; Aleksieieva, Anna; Eßwein, Alexander; Weigel, Robert; Vossiek, Martin (2011 IEEE MTT-S International Microwave Symposium, IMS 2011, 2011)
Recently, a novel ultra-wideband (UWB) local positioning concept based on pulsed frequency modulated (PFM) signals was introduced by the research groups of the authors of this paper. The current paper presents a detailed analysis of the performance - i.e. range and accuracy - of the proposed PFM-UWB approach. It is shown that with PFM-UWB an excellent coverage/range can be achieved. It is also shown that for high precision ranging a VCO with good phase-noise performance is needed. Based on simulations and measurement results the theoretical findings are verified. The results confirm that PFM-UWB allows for accuracy in the mm-range and a maximum range of more than 100 m with a measuring time of only 1 ms. © 2011 IEE
Keywords: radar; radio navigation; radio position measurement; transponders; Ultra-wideband (UWB)